Kriteria Keutamaan Kepuasan Pelanggan Terhadap Penghantaran Makanan Pihak ketiga Dalam Talian di Kalangan Generasi Wawasan Malaysia di UTHM - Ramlan, Rohaizan; Noor Liyana Zakaria (Research in Management of Technology and Business, 2021)
Objective this study is to indentify kriteria ranking customer satisfaction towards Online Food Delivery (OFD) service used Best Worst Method (BWM). The criteria are ease of use, effort expectency, innovativeness, social influence, convenience, Online experience, price saving and hedonic motivations. Quantitative method applied by disserminate survey to UTHM students that represent Malaysia’s “Wawasan Generation”. The Google Form disserminated throught WhatApps medium within two months starting November until December 2020. 156 form received, 13 form is not met the requirement. Therefore, only 139 form analysed using BWM method. The result shows criteria ranking that selected by respondent are ease of use, convenience, innovative, social influence, price saving, Online experience, effort expectency and hedonic motivations.